(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background: Drug-resistant pulmonary tuberculosis (DR-TB) remains one of the most significant challenges in global tuberculosis control. Treatment regimens for multidrug-resistant and extensively drug-resistant tuberculosis involve prolonged use of multiple anti-tuberculosis drugs, often resulting in adverse drug reactions (ADRs) that may affect treatment adherence and outcomes. Objective: To assess the frequency, spectrum, and clinical characteristics of adverse events associated with anti-tuberculosis medications in patients receiving treatment for drug-resistant pulmonary tuberculosis. Methods: A retrospective observational study was conducted involving 200 patients diagnosed with drug-resistant pulmonary tuberculosis. Adverse events were analyzed according to severity, affected organ systems, and implicated anti-tuberculosis drugs.